Sugar Cane Cake and Mineral Fertilizers on Coconut (Cocos nucifera Linn.) Seedlings - Luiz Gonzaga Bione Ferraz; Ademar Barros da Silva; Antonio Raimundo de Sousa; José Nunes Filho; Venézio Felipe dos Santos (International Coconut Community, 2009)
High quantities of mineral fertilizers (MF) are required for good coconut seedling production, whose up dated recommendation is 232 grams per seedling. The objective of this work was to assess the substitution of the MF by organic fertilizer as sugar-cane filter cake (SCFC) on coconut seedlings in polybag. The SCFC is an organic residue from sugar-cane manufacturing composed of various chemical elements, as for instance: nitrogen, phosphorus, potassium, calcium and magnesium. The experiment was carried out at the Itapirema Research Station, Goiana, Pernambuco State, Brazil, in a randomized complete block design, with factorial disposition 52, replicated three times, with six tall coconut seedlings per plot. The treatments were the combinations of five doses of MF (in g seedling-1): 46.25; 92.50; 138.75; 185.00 and control, using urea, simple superphosphate and potassium chloride at the proportion of 1:2:3, respectively, and five doses of SCFC (in kg polybag-1): 0.5; 1.0; 1.5; 2.0 and control. Eight months after young coconut seedlings replacement to the polybags the following parameters were measured: collar girth (CG), leaf area (LA), number of live leaves (NL) and plant height (PH). For leaf nutritional diagnosis and growing media chemical and physical analyses, samples were collected. There was significance for the two factors, individually, to all parameters. The trend analysis revealed linear, quadratic and cubic responses, according to the studied character. The mixture of 0.5 kg of SCFC polybag-1 plus 46.25 g of the MF was sufficient for obtaining seedlings of excellent quality and promoting a fertilizers economy around 80%. According to other results from this research, the number of seedlings per plot and the critical level of nutrients in the leaf of coconut seedlings should be reviewed.